2017
DOI: 10.1002/jca.21563
|View full text |Cite
|
Sign up to set email alerts
|

UK consensus statement on the use of plerixafor to facilitate autologous peripheral blood stem cell collection to support high‐dose chemoradiotherapy for patients with malignancy

Abstract: Plerixafor is a CXC chemokine receptor (CXCR4) antagonist that mobilizes stem cells in the peripheral blood. It is indicated (in combination with granulocyte-colony stimulating factor [G-CSF]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…Protocol 3 allowed us to obtain a significantly greater number of CD34+ cells than the other protocols: 7.93 × 10 6 CD34+ cells/kg vs 5.3 × 10 6 CD34+ cells/kg (protocol 1) and 4.28 × 10 6 CD34+ cells/kg (protocol 2). In other studies, this fact has also been suggested, either with the introduction of plerixafor [22][23][24][25][26] or with LVL. 2 In our country (Spain), there are no cost-benefit studies of mobilization protocols.…”
Section: Discussionmentioning
confidence: 97%
“…Protocol 3 allowed us to obtain a significantly greater number of CD34+ cells than the other protocols: 7.93 × 10 6 CD34+ cells/kg vs 5.3 × 10 6 CD34+ cells/kg (protocol 1) and 4.28 × 10 6 CD34+ cells/kg (protocol 2). In other studies, this fact has also been suggested, either with the introduction of plerixafor [22][23][24][25][26] or with LVL. 2 In our country (Spain), there are no cost-benefit studies of mobilization protocols.…”
Section: Discussionmentioning
confidence: 97%
“…Plerixafor is expensive and was used in selected cases. The administration of plerixafor is reported to be safe and efficacious in pediatric patients with a solid tumor, with mild adverse effects involving gut and injection site 34‐36 …”
Section: Discussionmentioning
confidence: 99%
“…However, all previous studies were done with healthy people. When considering the use of plerixafor in patients, based on the efficacy of plerixafor in two blinded randomized Phase III placebo‐controlled studies in patients with multiple myeloma and non‐Hodgkin lymphoma, current recommendations about this topic state that patients in a preemptive use protocol should receive a dose of plerixafor (0.24 mg/kg) after 4 to 5 days receiving G‐CSF (5‐10 μg/kg/day) and patients should start leukocytapheresis 10 to 12 hours after plerixafor administration . In real life, it means to administer plerixafor at 10:00 PM to capture the peak mobilizing effect 10 hours later, at 8:00 AM.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the use of plerixafor in patients, based on the efficacy of plerixafor in two blinded randomized Phase III placebo-controlled studies in patients with multiple myeloma and non-Hodgkin lymphoma, 6,7 current recommendations about this topic state that patients in a preemptive use protocol should receive a dose of plerixafor (0.24 mg/kg) after 4 to 5 days receiving G-CSF (5-10 μg/kg/ day) and patients should start leukocytapheresis 10 to 12 hours after plerixafor administration. 4,5,[23][24][25] In real life, it means to administer plerixafor at 10:00 PM to capture the peak mobilizing effect 10 hours later, at 8:00 AM. Because of this inconvenient timing, other authors administered plerixafor at 5:00 PM 11,26 or at 3:00 PM 12 and started leukocytapheresis the next day at 8:00 AM 11,12 or at 10:00 to 11:00 AM, 26 which means a delay of 15, 17, or up to 18 hours, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation